Black Velvet Art - Eliason, Eric A. (Eric Alden), 1967- (Book collections on Project MUSE., 2011)
Jesus, matadors, panthers, bandits, Indians, movie stars, waifs, and, of course, Elvis are recognized icons of the oft-despised, uber-kitsch art form of black velvet painting. In Black Velvet Art author Eric A. Eliason and photographer Scott Squire present a comprehensive overview of this covertly-loved and overtly-reviled tradition. In cooperation with a network of artists, collectors, importers, and gallery owners in Tijuana, Los Angeles, Seattle, and Calgary, this book draws from the largest survey of velvet painting ever undertaken. The book traces velvet's historical development as a folk.